Student Perceptions of the Talk Show Program "Ini Talkshow" on Net TV (A Quantitative Descriptive Study of Communication Science Students) - Habib, Muhammad Kurnia; Hidayat, Taufik Wal (Holistic Science, 2025)
This study aims to determine the perceptions of Communication Science students at Medan Area University towards the Ini Talk Show program on NET TV. This study uses a quantitative descriptive method with a random sampling technique in determining the sample. The study population was 380 Communication Science students at Medan Area University, class of 2022–2024, and a sample of 158 people was obtained. Based on the results of the study, it can be concluded that overall, the perception of Communication Science students at Medan Area University towards the Ini Talk Show program on NET TV received a positive response. This can be seen from respondents' assessments regarding the quality of the program, both in terms of the presenter and the themes/materials presented. The presenters were considered capable of entertaining the audience, while the themes/materials raised were considered quite entertaining and attracted the audience's attention.